BONE CONDENSATION WITH CRESTAL APPROACH IN A LIMITED CRESTAL OFFER - Vasile Nicolae (Romanian Journal of Oral Rehabilitation, 2015)
Aim of the study This study makes a synthesis of information from literature referred to bone condensation. The indications, techniques and effects of different procedures of bone consideration are presented below. Material and methods: 130 sinus augmentation procedures were undertaken on 60 consecutive patients (of 43- 50 and (26-69)years of age). The preoperative and postoperative radiologi¬cal study was developed by means of orthopantomography and CT. The survival rate of implants, as measured by inte¬gration and successfully loading, was compared between diffe¬rent graft materials, smoking/non-smoking patients, different groups of associated pathologies and simultaneous/delayed implants placement. The time (months) necessary for prost¬hetic loading was measured and compared between the differrent graft material groups. Discussions 220 screw-type implants were placed in sinus lifted regions. The average residual ridge height was 6,59±2,11 mm. The average postsurgical ridge height was 14,57±2,33 mm. After an average follow-up period of 2,94 years (range 1 to 5 years) the global implant survival rate was 96,91%. There has not been significant differences between diffe¬rent bone grafts, associated with comorbidity and smoking habits. Surgical preparation of the new socket focuses on achieving a stable anchorage for implants by obtaining primary stability and mainting it functional even after prosthetic loading.. Conclusions Making a retrospective of datas from literature, we have observed that the opinions are divided regarding the effect of bone condensing on primary stability of dental implants.